Utilization of Green Beans Vima 1 and Local as an Alternative Media Substitute Sabouraud Dextrose Agar (SDA) in the Growth of Trichophyton Rubrum - Widyanur; Retno Sasongkowati; Suliati (Jurnal Ilmiah Kesehatan, 2023)
Green beans are cultivated plants and crops with nutrients from vegetable protein. Varieties of mung beans vary, including Vima 1 and local. The fungus Trichophyton rubrum generates dermatophytosis. This research explored green beans and local Vima 1 as an alternative medium in the growth of Trichophyton rubrum fungus. The type of research used by laboratory experiments was carried out at the STIKes Hutama Abdi Husada Tulungagung Microbiology Laboratory in March - April 2022. SDA media and alternative media green beans Vima 1 and local variations of the mass of 6 grams and 7 grams inoculated Trichophyton rubrum fungus using a single dot method with repetition as much as five times. The results showed that Trichophyton rubrum fungus grows optimally on alternative media green beans Vima 1 variation of 7 grams of mass that grows colonies on the fifth day with an average final diameter of 14 mm. While alternative media green beans Vima 1 variation mass 6 grams 11 mm, SDA media 11.65 mm, alternative media local green beans variation mass 6 grams 7.5 mm, and variation mass 7 grams 11.5 mm. The result of independent statistical tests was a p-value < 0.00, which shows significant differences in each type of media. This study result concluded that green beans Vima 1 and local could be used as an alternative medium to replace the SDA media in the growth of Trichophyton rubrum fungus.